PENGEMBANGAN BAHAN AJAR MATEMATIKA MATERI SEGITIGA DENGAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIK PESERTA DIDIK SMP - Siti Kurnia Puspita; Achmad Mudrikah (Universitas Islam Nusantara, 2019)
This research is motivated by the lack of student’s mathematical understanding ability. The alternative to evercome thatproblem is developing the teaching material of mathematics learning by the discovery learning models. The purpose of thisresearch is arranging and developing the material learning that is valid and practice, finding out whether the use of teachingmaterial that is developed effectivelly in improving VII grade student’s mathematical understanding ability, and finding outthe respons of students to teaching materials. The research used the Research and Development method, by modificatingSugiyono’s R D model in teaching and learning design. The population in this research is VII grade the students. Thesample is a classes of them, class VII K as the product trial class, and class VII H as the usage trial class. The instrumentin the research are questionnaire for students and teacher, test for students, and observation sheet. The result of the researchshows that the teaching materials are valid and effective to improve student’s. The student’s responses are positive to theprocess of teaching and learning.